THE DOCTOR IS DISSATISFIED: PROFESSIONAL RIVALRY AMONG HEALTH PRACTITIONERS IN JOS UNIVERSITY TEACHING HOSPITAL, PLATEAU STATE, NIGERIA - Yale, Nalong Henry; Wash-Pam, Anna Awukun (African Journal of Social and Behavioural Sciences, 2025)
This study examines the consequences of professional rivalry among medical practitioners in Jos University Teaching Hospital. (JUTH) It analyses the differences among some healthcare specializations regarding their scope of practice and impact on patient care quality, patient outcomes, and overall healthcare delivery within the health sector. A qualitative research method was used through focus group discussions (FGD), in-depth interviews and key informant interviews conducted with participants who are doctors, nurses, pharmacists, and laboratory scientists affiliated with JUTH. The sample size of the study was twenty-eight (28); this depended on data saturation. The data was analyzed using themes. The findings indicate that hierarchical structures, power dynamics and turf wars, ambiguous and overlapping roles, perceived inequality in compensation and recognition and lack of effective communication are factors that affect relationships amongst medical professionals in JUTH. The study recommends enhanced communication and collaboration among healthcare professionals.